Three new synonyms of the spider Miagrammopes guttatus Mello-Leitão, 1937 (Araneae: Uloboridae) - Salvatierra, Lidianne; Tourinho, Ana Lúcia; Brescovit, Antonio D. (Zootaxa, 2011)
Miagrammopes correai Piza, 1944, M. zenzesi (Mello-Leitão, 1945) and M. lacteovittatus Mello-Leitão, 1947 are synonymized with Miagrammopes guttatus Mello-Leitão, 1937. Synonymies are based on morphological data from specimens recently collected compared with the recovered type of M. lacteovittatus, and the types M. correai and M. zenzesi, as well as data from original descriptions. The male of Miagrammopes guttatus is redescribed and the female is described for the first time. Lectotypes are designated for M. correai and M. lacteovittatus.